UPAYA PENGENTASAN STUNTING DENGAN PEMANFAATAN DIGITALISASI MEDIA DAN MAKANAN TAMBAHAN BERBASIS PANGAN LOKAL UNTUK PENINGKATAN STATUS GIZI TERINTEGRASI KKN UNAND - Yeffi Masnarivan; Yoko Masna Rivan M; Eris Agung Abdul Haris Sukas; Viony Elvis; Aris Abdullah Syauqi Yulson; Aulia Sasia Berlian; Salsabilla Al Khanza; Rahma Rani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Stunting remains a major malnutrition problem in Indonesia. The prevalence of stunting in West Sumatra in 2022 was higher than the national average prevalence (21.6%) which was 25.2%. Nagari Sungai Nyalo Mudiak Aia is one of the Nagari in Pesisir Selatan Regency, - including areas with stunting problems. This community service activity was conducted to address and overcome the issue of stunting through active participation in Posyandu activities. It was carried out from July to August 2024 using monitoring, counseling, and training methods for community health cadres and mothers of toddlers in Nagari Sungai Nyalo Mudiak Aia. Digital monitoring of toddlers' nutritional status revealed that 25 children (32.9%) were stunted, with 20 (26.3%) classified as moderately stunted and 5 (6.6%) as severely stunted. In addition, training was provided on the use of local food sources to meet toddlers’ nutritional needs. It is recommended that cadres always innovate in implementing integrated health posts to increase visits and the interest of toddlers’ parent in coming to integrated health POSYANDU.